Development and application of new nickel-based cholesteryl chloroformate gelator for the remediation of oil spillage in water - Raymond Tyoakaa Iorhemen; Abdulmumin Abdulkadir Nuhu; Israel Kehinde Omoniyi; Abubakar Babando Aliyu (Bulletin of the National Research Centre)
Abstract Background Oil spills have caused significant harm to human health, marine life, and the environment, prompting numerous remediation efforts but with limitations. This study explores the development of a nickel-based gelator (A(LS)2) for oil spill clean-up in water. The objectives used to achieve the aim of this study include: synthesis of a nickel metal complex linker unit (LU), synthesis of aromatic linker unit (AL) using an isophthaloyl chloride aromatic unit and LU, characterisation of the synthesised AL, and grafting of cholesteryl chloroformate in the AL to synthesise the gelator. The synthesised AL and gelator were coded NiAL and NiGe, respectively, and were characterised. Results Fragments of the synthesised compound corresponding to the proposed structure were found using GC–MS, and their diameters were 5.9 μm for NiAL and 47.0 μm for NiGe. FT-IR spectroscopy showed functional groups which include secondary amine and aromatic rings in NiGe, as well as secondary amine aromatic rings, alkane, and aromatic overtones in NiGe. Finally, TGA showed that NiGe was stable at temperatures up to 445 °C. NiGe formed a gel with petroleum motor spirit (PMS), kerosene (KSE), and crude oil (COL) in a maximum time of 6.5 min. The Tgel (at 2 mg) value and sorption capacities were 44 °C and 5.8 ± 0.8 gg−1 for KSE, 39 °C and 3.7 ± 0.2 gg−1 for PMS, and 58 °C and 4.2 ± 0.7 gg−1, respectively. NiGe had a removal efficiency of 92% for COL, 90% for PMS, and 84% for KSE. NiGe could be recycled for up to five cycles. For better results, 0.5 g of NiGe formed gels with 4.20 mL of KSE, 4.60 mL of PMS and 5.42 mL of COL, which were subsequently removed from polluted water. Nickel-based organometallogelator (NiGe) was successfully synthesised and applied for oil spill clean-up in water; the gelator remediated crude oil, petroleum motor spirit and kerosene, respectively, from contaminated water; NiGe CuGe is recyclable; hence, scooped oil can be recovered and CuGe reused for several cycles, and oleophilicity makes CuGe, which is thermally stable and selective, best in biphasic oil–water mixture separation. Conclusions A nickel-based gelator with an A(LS)2 network, which is stable at high temperatures, environmentally friendly, crystalline, and recyclable, has been successfully synthesised and used to remove KSE, PMS, and COL from water.